Drug Prescribing to the Elderly Patients - A, Misha’l Aly (International Journal of Human and Health Sciences (IJHHS), 2018)
Age-related physiologic and anatomic changes in various body systems are accompanied by significant pharmacokinetic and pharmacodynamic alterations that make it mandatory for treating physicians to adjust types and dosages of medications for their older patients. Moreover, physicians should be always alert for adverse drug events, and consider any new symptoms as drug-related until proven otherwise. Other issues addressed include prescribing cascades, polypharmacy, drug-drug interactions, and the need to review all medications used by the elderly patients, with special attention to non-prescription and herbetic drugs. This review aims at maximizing safe medicine prescribing, and minimizing adverse drug event in caring for older subjects. International Journal of Human and Health Sciences Vol. 01 No. 02 July’17. Page : 65-69